The Association of Interleukin-6 (IL-6) -572G/C and Transforming Growth Factor Beta 1 (TGFB1) 29C/T Single Nucleotide Polymorphisms (SNPs) with Developmental Dysplasia of the Hip: a Case Control Study - (:unkn) unknown (My University, 2021)
PURPOSE OF THE STUDY The aim of the present study was to determine the potential effects of single nucleotide polymorphisms (SNPs) of TGFB1 and IL-6 on the development and severity of the disease in patients with DDH and investigate the relationship of these two gene polymorphisms. MATERIAL AND METHODS This case control study was conducted on 105 patients diagnosed with DDH and 119 healthy control subjects of any age. The DDH patients were classified according to the Hartofilakidis and IHDI classifications for adult and pediatric patients, respectively. Genomic DNA was isolated from peripheral blood samples using the Salting-out method. TGFB1 gene p.Pro10Leu (c.29C>T) (rs1800470) and IL-6 572G>C (rs1800796) polymorphisms were analyzed using Sanger DNA sequencing. RESULTS There was no statistically significant relationship of TGFB1 and IL-6 SNPs for DDH. When the rs1800470 and rs1800796 polymorphisms were compared according to family history, the homozygous mutation rate of TGFB1 gene was found to be significantly higher in patients with a positive family history than in patients with a negative family history. No significant relationship was found between rs1800796 polymorphisms and family history. TGFB1 homozygous mutation rate was determined to be statistically higher in the positive family history group than control group. No similar relationship was found between the negative family history group and the control group. No statistically significant relationship was determined between rs1800470 and rs1800796 and the severity of DDH. CONCLUSIONS rs1800796 and rs1800470 polymorphisms do not appear to be major responsible genetic factors for DDH. However, the determination of a correlation between a positive family history and homozygous mutation rate of the TGFB1 gene indicates that this gene may have a greater effect on DDH development. Key words: developmental dysplasia of the hip, interleukin-6, transforming growth factor beta 1, case control study.
Keywords: Adult; Humans; Child; Case-Control Studies; Gene Frequency; Polymorphism, Single Nucleotide; Interleukin-6; Transforming Growth Factor beta1; Developmental Dysplasia of the Hip